2004
DOI: 10.1016/j.cub.2004.03.033
|View full text |Cite
|
Sign up to set email alerts
|

A Component of C. elegans Meiotic Chromosome Axes at the Interface of Homolog Alignment, Synapsis, Nuclear Reorganization, and Recombination

Abstract: A universal feature of meiotic prophase is the pairing of homologous chromosomes, a fundamental prerequisite for the successful completion of all subsequent meiotic events. HIM-3 is a Caenorhabditis elegans meiosis-specific non-cohesin component of chromosome axes that is required for synapsis. Our characterization of new him-3 alleles reveals previously unknown functions for the protein. HIM-3 is required for the establishment of initial contacts between homologs, for the nuclear reorganization characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
237
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(249 citation statements)
references
References 21 publications
10
237
0
1
Order By: Relevance
“…The protein Zyp1 of A. thaliana is a component of the transverse filaments of the SC (Higgins et al 2005) and has been shown to have equivalent proteins in yeast (Sym et al 1993), mammals (Heyting 1996), Caenorhabditis elegans (Couteau et al 2004), and D. melanogaster (Page and Hawley 2004). Antibodies raised against these two proteins of A. thaliana were used in this study to monitor and compare the assembly of bivalents in wild type and its synaptic mutant sy10.…”
Section: Discussionmentioning
confidence: 99%
“…The protein Zyp1 of A. thaliana is a component of the transverse filaments of the SC (Higgins et al 2005) and has been shown to have equivalent proteins in yeast (Sym et al 1993), mammals (Heyting 1996), Caenorhabditis elegans (Couteau et al 2004), and D. melanogaster (Page and Hawley 2004). Antibodies raised against these two proteins of A. thaliana were used in this study to monitor and compare the assembly of bivalents in wild type and its synaptic mutant sy10.…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that a protein complex comprising Hop1, Red1, and Mek1 is instrumental in establishing interhomolog bias by virtue of its capacity to actively prevent Rad51-mediated intersister chromatid repair (Hollingsworth and Ponte 1997;Woltering et al 2000;Niu et al 2005). It has also been proposed that HIM-3, a protein that is related to Hop1 on the basis that it contains a HORMA domain and is a component of chromosome axes, may also prevent the use of sister chromatids for repair during meiosis in Caenorhabditis elegans (Zetka et al 1999;Couteau et al 2004).…”
mentioning
confidence: 99%
“…In addition, for a crossover to generate a chiasma, the crossover must occur between homologs and not between sisters. Thus, there appears to be a barrier (or semipermeable barrier) between the sister chromatids that promotes homolog exchange, possibly involving the activity of chromosome axis proteins (Couteau et al 2004;Webber et al 2004;Niu et al 2005;Kim et al 2010;Li et al 2011). Finally, homologous repair must be promoted while more error-prone mechanisms that could introduce de novo mutations in the germline such as nonhomologous end joining (NHEJ) are inhibited.…”
mentioning
confidence: 99%